ANXIETY OF ENNIS DEL MAR REFLECTED IN ANG LEE'S BROKEBACK MOUNTAIN: A PSYCHOANALYTIC APPROACH - Sari , Bayu Novita (2007)
The major problem of this study is how anxiety reflected on the major character personality. The objectives of this study are to analyze the movie based on the structural element and to analyze anxiety on Ang Lee's Brokeback Mountain based on psychoanalytic analysis. This study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Brokeback Mountain a movie by Ang Lee. The data sources are primary and secondary data sources. The primary data sources is the movie itself, Brokeback Mountain, and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive qualitative analysis. Based on the analysis, the writer concludes that, 1) the problem faced by the major character is his struggle to reach his true love and keep the secret of that love, because it is forbidden love. It causes him lived with anxiety, because he always tries to hide his true identity. 2) The superego dominates more Ennis's personality than his id in taking decision. So that he fells more anxious of social punishment, because his decision always considers moral and social norms.